Answer:
82
Step-by-step explanation:
49 - 3 + 72/2
= 46 + 36
= 82
I added 8 on both sides to get 12=3x then I divided by 3 on both sides to get x=4
9514 1404 393
Answer:
a^4·m^4·n^8
Step-by-step explanation:
The applicable rule of exponents is ...
(a^b)(a^c) = a^(b+c)
__
m^2n^3 aanm^2a^2n^4
= a^(1+1+2)·m^(2+2)·n^(3+1+4)
= a^4·m^4·n^8
Answer:
A, B, F
Step-by-step explanation:
2/3 - x + 1/6 = 6x
Collect like terms
2/3 + 1/6 = 6x + x
(4+1) / 6 = 7x
5/6 = 7x
x = 5/6 ÷ 7
= 5/6 × 1/7
x = 5/42
a) 4 - 6x + 1 = 36x
4 + 1 = 36x + 6x
5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
b) 5/6 - x = 6x
5/6 = 6x + x
5/6 = 7x
This is equivalent to the third step of the simplification
c) 4 - x + 1 = 6x
4 + 1 = 6x + x
5 = 7x
x = 5/7
Not equivalent to any of the steps in the simplification above
d) 5/6 + x = 6x
5/6 = 6x - x
5/6 = 5x
x = 5/6 ÷ 5
= 5/6 × 1/5
x = 5/30
Not equivalent to any of the steps in the simplification above
e) 5 = 30x
x = 5/30
Not equivalent to any of the steps in the simplification above
f) 5 = 42x
x = 5/42
Equivalent to the last step of the simplification above
Y = 4x + 3 ---------(1)
y = -x - 2 ---------(2)
Subtract (2) from (1), you get
0 = 5x + 5
⇒ 5x + 5 = 0
⇒ 5x = -5
⇒ x = -5/5 = -1
y = -(-1) - 2 = -1
Answer is (-1,-1)